Exploring the halo occupation of AGN using dark-matter cosmological simulations. Issue 1 (20th December 2018) - Georgakakis, A; Comparat, J; Merloni, A; Ciesla, L; Aird, J; Finoguenov, A
ABSTRACT: A semi-empirical model is presented that describes the distribution of active galactic nuclei (AGNs) on the cosmic web. It populates dark-matter haloes in N -body simulations (MultiDark) with galaxy stellar masses using empirical relations based on abundance matching techniques, and then paints accretion events on these galaxies using state-of-the-art measurements of the AGN occupation of galaxies. The explicit assumption is that the large-scale distribution of AGN is independent of the physics of black hole fuelling. The model is shown to be consistent with current measurements of the two-point correlation function of AGN samples. It is then used to make inferences on the halo occupation of the AGN population. Mock AGNs are found in haloes with a broad distribution of masses with a mode of${≈ } 10^{12}\, h^{-1} \, M_{\odot }$ and a tail extending to cluster-size haloes. The clustering properties of the model AGN depend only weakly on accretion luminosity and redshift. The fraction of satellite AGN in the model increases steeply toward more massive haloes, in contrast with some recent observational results. This discrepancy, if confirmed, could point to a dependence of the halo occupation of AGN on the physics of black hole fuelling.